2014
DOI: 10.1016/j.compedu.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic outlining as a writing strategy: Effects on students' writing products, mental effort and writing process

Abstract: a b s t r a c tThis study addresses to what extent and how electronic outlining enhances students' writing performance. To this end, the focus of this study is not only on students' final writing products but also on the organisation of the writing process (i.e., planning, translating, and reviewing) and perceived mental effort during writing. In addition, effects of repeated electronic outlining were examined. A combined within and between subjects design was implemented in which 93 10th-grade students wrote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 52 publications
6
35
2
Order By: Relevance
“…Furthermore, we have found that the use of sources in the beginning of the writing process is important. We can relate these findings to numerous planning studies in L1 and L2 (De Smet et al 2014;Ellis & Yuan, 2004;Johnson et al, 2012;Limpo & Alves, 2018).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, we have found that the use of sources in the beginning of the writing process is important. We can relate these findings to numerous planning studies in L1 and L2 (De Smet et al 2014;Ellis & Yuan, 2004;Johnson et al, 2012;Limpo & Alves, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Initial planning before writing leads to higher quality texts in L1, but might be attributed to longer time on task (Ellis & Yuan, 2004;Johnson, Mercado, & Acevedo, 2012). Furthermore, planning tends to increase the writing fluency (i.e., production rate per minute; De Smet et al 2014;Limpo & Alves, 2018). In L2, preplanning has a beneficial effect on fluency (Ellis & Yuan, 2004;Johnson, Mercado, & Acevedo, 2012) and linguistic complexity (Ellis & Yuan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the sessions participants were asked to fill out a questionnaire on writing styles created by Kieft et al (2006) in order to determine their writing preference. We chose this particular questionnaire because it has been tested and used in writing research extensively (e.g., Kieft et al, 2008;Tillema, 2012;De Smet et al, 2014;Van der Loo et al, 2018). The writing style questionnaire measures reported degrees of planning and revising styles and consisted of 36 items: 13 items reported planning-type behavior, 12 items reported revising-type behavior and the remaining 11 items were fillers.…”
Section: Writing Style Questionnairementioning
confidence: 99%
“… 2. It bears mention that outlining can be used for writing rather than for improving comprehension of text or lecture material. Learner-generated outlining without prior training facilitates essay writing by improving the structure of the written product and it appears to reduce mental effort (De Smet, Brand-Gruwel, Leijten, & Kirschner, 2014; De Smet, Broekkamp, Brand-Gruwel, & Kirschner, 2011; Kellogg, 1990; but see De Smet, Brand-Gruwel, Broekkamp, & Kirschner, 2012). …”
mentioning
confidence: 99%